Sosialisasi Tentang Sistem Pemerintahan Adat Yapio Patai di Elpaputih, Kabupaten Seram Bagian Barat - Pietersz, Jemmy Jefry; Picauly, Benjamin Carel; Saija, Vica Jillyan Edsti; Kuahaty, Sarah Selfina (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: On Seram Island, there is an association of customary law communities who live in groups in a certain form, known in the Wemale language as "Yapio Patai". Yapio means looking, and seeing, while Patai means fellowship. Yapio Patai is a form of customary law community association consisting of 38 families/clans. This alliance has not been regulated in the current village/state government system based on statutory regulations.Purposes of Devotion: The purpose of this article is to convey the results of socialization which is the result of previous research, that Yapio Patai can be categorized as a Fam/Clan Confederation. Method of Devotion: This activity was carried out using the method of socializing the law to the public based on the results of previous research by the team, which was carried out empirically.Results of the Devotion: The results of the service show that Yapio Patai is still accepted by the people of the Yapio Patai alliance as a form of traditional government that continues to live and function amid the alliance. The existence of Yapio Patai is a fam/clan confederation consisting of 38 fam/clans, which still exist even though they are spread across 7 hamlets or villages.